Analisis Pembentukan Portofolio Optimal Saham Saham Di Indeks Saham LQ-45 Menggunakan Model Elton Dan Gruber Periode 2019-2024 - Sandi, Samuel; Husadha, Cahyadi; Kurniawan, Dody (CV. KAMPUS AKADEMIK PUBLISING, 2025)
This study aims to analyze the formation of an optimal portfolio of stocks included in the LQ-45 index on the Indonesia Stock Exchange using the Elton and Gruber Models for the 2019-2024 period. The Elton and Gruber Models were chosen because of their ability to simplify the portfolio selection process through a trade-off approach between return and risk, without requiring a complex covariance matrix. This research method uses a quantitative approach with secondary data in the form of monthly stock prices, market return rates, and risk-free interest rates. The results of the study indicate that stock selection based on the excess return to beta ratio produces a more efficient portfolio compared to the traditional approach. In addition, the composition of the optimal portfolio produced is able to provide competitive returns with a diversified level of risk. These findings are expected to contribute to investors in making more rational investment decisions based on empirical data..